KEGIATAN EKSTRAKURIKULER BAND DI SMK NEGERI 1 PAYAKUMBUH - Nindia Khaira Putri Ramadhani; Hadi, Harisnal (Universitas Negeri Padang, 2026)
The research on the band extracurricular activities at SMK Negeri 1 Payakumbuh aims to describe and explain the implementation of the band extracurricular activities at the school. The method used in this research is the descriptive method, which is part of qualitative research methods. The data collection techniques used in this study include observation, interviews, documentation, and conducting a documentation study, the results of which will be explained in the research. The data obtained are analyzed by grouping data, evaluating data, explaining data, and drawing conclusions. The results of this research indicate that extracurricular band activities at SMK Negeri 1 Payakumbuh have been conducted regularly since 2023. However, the implementation of these activities has not yet run optimally. This is marked by the low attendance of students and the suboptimal role of the supervisors in providing guidance, technical assistance, and activity evaluations, causing the activities to not follow the planned program. In addition, limited practice time, inadequate rehearsal space, and the divided focus of the supervisors have become obstacles in the implementation of the activities.